ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KUALITAS LAYANAN PENDIDIKAN DI SMK SASMITA JAYA 2 - Zubaidah, Siti; Murtiyoko, Heri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the influence of organizational culture on the quality of educational services at SMK Sasmita Jaya 2. The background of this study is based on the importance of creating a school environment with a positive work culture as a strategic factor in improving the quality of educational services. The method used in this study is a quantitative approach with Pearson's correlation technique. The research instrument consists of a Likert scale questionnaire comprising 30 statements for each variable and was distributed to 50 respondents, including teachers and educational staff. Before conducting the correlation analysis, the data was tested through prerequisite tests, namely linearity and normality tests. The results indicate that the relationship between organizational culture and service quality is linear, and the data are normally distributed. The correlation analysis revealed a coefficient value of 0.960 with a significance level of 0.000, indicating a very strong and statistically significant relationship between the two variables. This finding suggests that strengthening organizational culture contributes significantly to improving the quality of educational services. This study recommends the importance of developing a collaborative, adaptive, and quality-oriented organizational culture as a strategy for improving services in vocational school environments.